PEMANFAATAN SISTEM INFORMASI PENJADWALAN MATA PELAJARAN PADA SMA SANTO FRANSISKUS ASISI PONTIANAK - Genrawan Hoendarto; Alfred Putra; Hardiyanto Candra (LPPM Universitas Widya Dharma Pontianak, 2021)
he rapid development of information technology in the current era of globalization has provided many benefits in advancing various social aspects. The development of information technology has a very important role in an effort to create progress in all fields intended for human interests in general. Information systems are also one of the important parts for companies in increasing productivity, both in obtaining information, processing, and using this information, especially for the interests of the company itself.The method used in this study uses descriptive method, observation and literature study. Descriptive method is a method used to describe or analyze a research result but is not used to make broader conclusions. Observation is a systematic observation and recording of the elements that appear in a symptom or symptoms in the object of research. Literature study is a method of collecting various kinds of data contained in the library, such as newspapers, books, magazines, manuscripts, documents and so on that are relevant to research.This study produced a design of an information scheduling system for each class, the application of information systems scheduling these subjects using the Unified Modeling Language (UML) modeling. By using the SQL Server 2008 R2 database, and using the Microsoft Visual Studio 2012 programming language. When the curriculum only inputs data into the application system, the schedule will be arranged automatically in the system. Arranged schedules will be saved into the SQL Server database and displayed in the Crystal Report.Based on the results of the discussion of the analysis and design of the subject scheduling information system at SMA Santo Fransisikus Asisi, it can be concluded that subject scheduling activities can shorten schedule processing time. Scheduling these subjects is also designed with a display that is easy to understand and easy to use by users. Keywords: Scheduling, Information Systems, High Schools